MENGAPA HARUS GANTI LOGO? (Kasus Pergantian Logo PT Pertamina dan Bank BNI ditinjau dari aspek Filosofi, Estetika dan Fungsional) - Wibowo - (DeKaVe, 2012)
The more professional a company, the role of corporate identity or logo increasingly important,especially for the needs of sales promotion, public relations, publicity, and advertising.. Besides aiming tobuild the companies image in the public eye, a good logo will lead to suggestions and strong selfconfidence,pride, sense of belonging, even to establish unity and solidarity among the members of oneanother.